Electronics in advanced research industries : industry 4.0 to industry 5.0 advances - Massaro, Alessandro, 1974- (Hoboken, NJ, USA : Wiley, 2022)
"Electronics in Advanced Research Industries: Industry 4.0 to Industry 5.0 Advances introduces smarter ways of developing machine control. The author - a noted expert on the topic - combines smart technology such as Industry of Things, artificial intelligence (AI) and nanotechnology with the likes of robotic machines, machine to machine interfaces and approaches to design production. Electronics in Advanced Research Industries is comprised of nine chapters, each one including examples and diagrams for the reader to interact with. Sub-categories are also implemented throughout every chapter, detailed and precise findings from a scientific expert researcher in the subject. This book is a single-authored book which connects electrical and mechanical engineering in a unique way to ensure we are producing the best designed technology possible"--
BIBINDX
Keywords: Industry 4.0.; Automation; Electronic books